The Effect Of Different Weight Percentages Of Lead (II) Oxide Nanoparticles Based Solid Polymer Electrolyte Towards Tonis Conductivity. - Chong, Mee Yoke; Arshid, Numan; Ramesh, K.; Ramesh, S. (2016)
The solid polymer electrolyte (SPE) film based on hydroxylethyl cellulose, magnesium triflate, 1-ethyl-3- methylimidazolium and lead(II) oxide nanoparticles was prepared by solution casting technique. The SPE formed exhibits low ionic conductivity at room temperature, hence various weight percentages (1%, 2%, 3% and 4%) of lead(II) oxide nanoparticles is incorporated into the SPE to enhance the conductivity. By conductivity studies it revealed that the maximum ionic conductivity of 4.9910-4 S cm-1 is achieved for SPE with 3 wt. % of lead(II) oxide nanoparticles at room temperature. All the SPEs obeyed Arrhenius theory.